Increasing PhD students' employability by focusing on the academic entrepreneurship. The analysis of the entrepreneurial competences - Sabina Hodzic (Universidad de Deusto, 2016)
The aim of the present study was to explore the perspective for entrepreneurship among PhD students coming from variety of disciplines. More precisely, to identify the most important entrepreneurial competences for succeeding in the entrepreneurial venture, to explore whether these competences are being developed during the 3rd cycle studies, and to explore the entrepreneurial intentions of the future doctors. In order to choose the most important entrepreneurial competences, individual semi-structured interviews with ten entrepreneurs from different fields were conducted. In addition, the importance of each competence was evaluated in form of the questionnaire, by seventeen entrepreneurs. After the qualitative and quantitative analysis of the interviews and the questionnaire, 20 competences were selected as the most important entrepreneurial competences. These 20 competences were then evaluated by 50 PhD students from different fields of study. They evaluated the importance of each entrepreneurial competence, the level of its development during their PhD studies, and indicated their entrepreneurial intentions after finishing the PhD. The most important and the most developed competences are presented in the results. In addition, the results showed relatively high entrepreneurial intentions in case of not finding a job after the PhD and in general. These results imply the need for incorporating some sort of entrepreneurial training and the development of entrepreneurial competences adapted to each subject area during the PhD studies. Published online: 01 June 2016